SWOT Analysis and Value Proposition Canvas as a Business Development Strategy for Tirta Sasmita Mineral Water - I Gede Marendra; Aryata, I Made; Tua, Rudy Bodewyn Mangasa (PT FORMOSA CENDEKIA GLOBAL, 2023)
The mineral water business is a very interesting business, this is because the growth potential is projected to continue to increase every year, so it is not surprising that many companies are involved in the (AMDK) business, including CV. Tirta Sasmita which produces Tirta Sasmita Drinking Water. The large number of manufacturers in the AMDK business makes competition in the AMDK business increasingly tough, so it is important for companies to have a strategy to face business competition. One method that can be used to create a business development strategy is through SWOT Analysis and Value Proposition Canvas. From the results of the research carried out, it is known that the strategy is a Growth Strategy with activities that can be carried out including: 1) Carry out Market Penetration through optimizing Product Branding; 2) Penetrating the market through the